The Little Mermaid II - Return to the Sea - Smith, Jim Kammerud Brian; Benson, Jodi, 1961-; Samuel E Wright; Tara Strong; Pat Carroll; Buddy Hackett (Walt Disney Video, 2000)
Ariel and her husband, Prince Eric, have a little problem with their daughter, Melody, in the sequel to Disney's landmark
Languages : English, French, Spanish
Subtitles : English, Spanish
Keywords: Kids -- Musical -- Family -- Adventure -- Fantasy; Animation